GENDER VARIATION IN ANGULATIONS OF IMPACTED THIRD MOLARS: A RETROSPECTIVE STUDY - Pranati T; Dr. Madhulaxmi Marimuthu; Dr. Adimulapu Hima Sandeep (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Impacted third molars and their removal os one of the most common outpatient procedures done by oral and maxillofacial surgeons. The aim of this retrospective study was to analyse the prevalence and gender variations of angulations pertaining to impacted third molars among patients who have undergone trans alveolar extraction for the same. Retrospective study was conducted and data collection was done from June 2019 to April 2020. Winter’s Classification of impaction, age & gender of all the patients who underwent extraction procedure for impacted third molars were recorded. Data was imported to IBM SPSS Version 20 for statistical analysis. Results were tabulated. Prevalence of third molar impaction was more among males (57.6%) compared to females (42.4%). Prevalence was more among patients belonging to the third decade of life (57.4%). Majority of the study population (87.9%) had single tooth impaction. Mandibular molars had higher chances of impaction (91.7%) than maxillary molars (8.3%) and 38 (30.8%) being the most commonly impacted tooth. mesioangular impaction was the most common type of impaction (43.5%) This study shows that the prevalence of third molar impaction is more among males compared to females . Mandibular molars have higher chances of impaction than maxillary molars and Mesioangular impaction being the most common type of impaction. Prevalence is more among patients belonging to the third decade of life. These results are in accordance with the several studies conducted in the same geographical location